INCLUSION OF IMMUNOTROPIC DRUGS INTO THE PHARMACOLOGICAL THERAPY OF ORAL LICHEN PLANUS - DS Tishkov (Journal of Global Pharma Technology, 2016)
Lichen planus (LP) is one of the most common diseases of oral mucosa (OM). It is characterized by recurrent, persistent course and a great variety of forms.